2007
DOI: 10.1007/s00104-007-1436-z
|View full text |Cite
|
Sign up to set email alerts
|

Komplexe proximale Humerusfraktur beim alten Menschen

Abstract: Compared to SHA, functional outcome was superior with FAPF. However, this was associated with a higher rate of revision surgery. Most patients were still able to live independently in their original environment, regardless of the type of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 31 publications
0
11
0
4
Order By: Relevance
“…When approaching this kind of complex fracture, the choice is between joint replacement by use of a prosthesis [1] or reduction and fixation (by use of plates and screws or K-wires) [2]. The surgical technique is demanding and the outcomes are not so good in both cases.…”
Section: Introductionmentioning
confidence: 99%
“…When approaching this kind of complex fracture, the choice is between joint replacement by use of a prosthesis [1] or reduction and fixation (by use of plates and screws or K-wires) [2]. The surgical technique is demanding and the outcomes are not so good in both cases.…”
Section: Introductionmentioning
confidence: 99%
“…Neer recommended open reduction and internal fixation (ORIF) for three-part fracture-dislocations and primary hemiarthroplasty (HA) for four-part fracturedislocations and for fractures with greater than 50% of cartilage-covered articular defect [24,25]. Angular stable implants have been developed for fractures of the proximal humerus [7,9,10,23,30]. With these implants, better biomechanical stability could be achieved [16].…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study from our institution found hemiarthroplasty for acute three-and four-part proximal humerus fractures resulted in effective pain relief but less predictable function and ROM [11]. Dietrich et al [6] and Solberg et al [24] independently observed function is better with locking plate fixation compared to hemiarthroplasty but found no difference in pain reported between the two treatment groups and found a greater incidence of revision surgery/ complications in patients treated operatively.…”
Section: Discussionmentioning
confidence: 96%
“…In a previous study, we examined the early complications of proximal humerus fractures treated with locking plates; 24% of patients had complications and a majority of these were related to intra-articular penetration of screws into the glenohumeral joint [7]. Locking plates reportedly provide comparable ROM, subjective scoring, and pain relief to other forms of fixation and reportedly are associated with better ROM compared to hemiarthroplasty with variable pain relief [2,6,12,24].…”
Section: Introductionmentioning
confidence: 99%